Health Status and Association With Interpersonal Relationships Among Chinese Children From Urban Migrant to Rural Left-Behind - Zhao, Guanlan; Wang, Menmen; Xu, Jiayao; Lu, Jingjing; Akezhuoli, Hailati; Wang, Feng (Frontiers in Public Health, 2022)
Background To date, numerous studies have examined the health status of Chinese left-behind children and migrant children. However, the impact of children’s diverse migration/ left-behind experiences on their health is still unclear. Methods A cross-sectional survey was conducted in 2020 in Nanling country (Anhui province) and Kaihua country (Zhejiang province) in China. School children from grade 5 to 8 reported their socio-demographic, interpersonal relationships, self-rated health, suicidal ideation, and depression. Participants were divided into four groups based on their migrant patterns, namely rural left-behind children with previous migration experience (ME-LBC), rural children with previous migration experience (ME-NLBC), rural left-behind children without migration experience (LBC), and rural children without migration experience (NLBC). Results Among 2323 participants included in the present study, there were 336 ME-LBC (14.5%), 283 ME-NLBC (12.2%), 561 LBC (24.1%) and 1143 NLBC (49.2%). Compared with NLBC, ME-LBC reported significantly poorer self-rated health (OR=0.72, 95% CI [0.53-0.97], p<0.05), higher risk of depression (β=0.90, 95% CI [0.02-1.77], p<0.05) with adjustment of socio-demographic and interpersonal relationships. There was no significant difference in suicidal ideation among different groups of children. The better interpersonal relationship was associated with a better self-rated health, and lower prevalence of depression and suicidal intention. Conclusions Compared to ordinary rural children, ME-LBC tended to experience higher levels of depression and poorer self-rated health. These research findings imply developing intervention programs about psychological adjustment tailored to different migrant patterns of Chinese rural children. The keys might be to strengthen the relationships with peer and teacher in school and improve the quality of parent-child communication in family for LBC.